Prevalence and correlates of polycystic ovarian syndrome among women attending infertility clinic - Tusimin, Maiza (American Journal of Human Sciences and Social Research (ARJHSS), 2018)
Polycystic ovarian syndrome (PCOS) is a complex endocrine disorder which affects 5% to10% of women worldwide. The disease is caused by insulin resistant that results in hyperinsulinaemia, and further stimulates the excessive production of androgen and luteinizing hormone. Hyperandrogenism which is referred to the excessive production of androgen leads to the clinical conditions like acne, obesity, alopecia and irregular menstruation. Previous studies have shown the risk factors of PCOS include age, ethnicity, obesity, smoking, alcohol consumption and menstrual problem. A cross sectional study was conducted at infertility clinic in Hospital Serdang. Simple random sampling was adopted to recruit 138 women who attended the infertile clinic. Data including sociodemographic data, lifestyle factors, medical disorders, gynaecology disorders, family medical history, menstrual problem, diagnostic criteria of PCOS, metabolic parameters, and causes of infertility, were retrieved from medical record. Chi square test and SPSS version 21 was used for data analysis. Among 138 participants, 37.7% are diagnosed with PCOS and 62.3% are not diagnosed with PCOS. Among PCOS patients, 92.3% are found to age less than 35 years old, 90.4% Malay, 75% with menstrual problem and 80.8% obese. Age, menstrual problem, and obesity were significantly associated with PCOS diagnosis. Measures like medical education and healthy lifestyle should be implemented to prevent the complications of PCOS.